2013
DOI: 10.1111/jam.12227
|View full text |Cite
|
Sign up to set email alerts
|

Micronized benzoic acid decreases the concentration necessary to preserve acidic beverages against Alicyclobacillus

Abstract: Aims: The aim of this study was a challenge testing the effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The solubility of benzoic acid is not good in water; therefore, it is less effective. Benzoate is more popular as a food preservative, while Kawase and others () produced micronized benzoic acid, using an experimental unit, and found that the smaller shape (10 to 200 μm by SEM, regular shape) was more effective against A. acidoterrestris compared with common commercial sodium benzoate and benzoic acid (up to 500 μm by SEM, irregular shape), and the concentration of which was doubled. The bactericidal effect of micronized benzoic acid mainly included the lysis of cells/spores and intracellular material's exposure.…”
Section: Chemical Intervention Treatmentsmentioning
confidence: 99%
“…The solubility of benzoic acid is not good in water; therefore, it is less effective. Benzoate is more popular as a food preservative, while Kawase and others () produced micronized benzoic acid, using an experimental unit, and found that the smaller shape (10 to 200 μm by SEM, regular shape) was more effective against A. acidoterrestris compared with common commercial sodium benzoate and benzoic acid (up to 500 μm by SEM, irregular shape), and the concentration of which was doubled. The bactericidal effect of micronized benzoic acid mainly included the lysis of cells/spores and intracellular material's exposure.…”
Section: Chemical Intervention Treatmentsmentioning
confidence: 99%
“…Strain CZB-12 was isolated from the whole production line of kiwi products in China whereas strains XC-6 and FB-40 were identified in maize juice and in the debris from the factory floor respectively. The DNA sequences of the second block, composed of 7 isolates (C21-C1), matched with strains XC-6 (accession number: KJ158157) and FB40 (accession number: KF880723) ( Table 3 ) Finally the third block was formed by 4 isolates (C6-C15) that share a good percentage of identity with strains CBZ-12 [ 33 ] and strain UFRRJAT1 [ 34 ] found in orange juice ( Table 3 ). This distribution is intriguing since it is possible to speculate that soil isolates were clustered in effectively soil species and isolates that are moving from soil to other possible growing source characterized by parameters, like pH, that could strong influence bacterial survive.…”
Section: Resultsmentioning
confidence: 96%